Portraits of Antun Gustav Matoš by Josip Vaništa and Antun Babić - Kusik, Vlastimir (Poznańskie Studia Slawistyczne, 2014)
This essay deals with two visual art portraits by the painter Josip Vaništa and the sculptor Antun Babić. The subject is Antun Gustav Matoš, whom each artist depicts according to his own artistic vocabulary and visual language. There is a difference in both the form and the motivation. For Josip Vaništa, A.G. Matoš announced the dawn of Croatian modernism, which was his painterly point of departure, while for A. Babić, A.G. Matoš was a literary figure who belonged to s specific physical space.